Expert Based Ecosystem Service Assessment in Coastal and Marine Planning and Management: A Baltic Lagoon Case Study - Schernewski, Gerald; Inácio, Miguel; Nazemtseva, Yaroslava (Frontiers in Environmental Science, 2018)
The assessment of ecosystem services, the benefits humans obtain from ecosystems, is a worldwide topic of growing interest, but examples addressing coastal and marine water are still a small minority. In this study, we carry out an expert based ecosystem service assessment for a concrete case study, the Szczecin (Oder) Lagoon located at the German/Polish border in the Baltic Sea region. We analyze to what extent, in which step and how it can be applied for supporting Integrated Coastal Zone Management (ICZM), the ecological-social-economic assessment within System Approach Frameworks (SAF) and Marine Spatial Planning (MSP). The large, shallow Szczecin Lagoon is heavily eutrophied. Therefore, several alternative measures (scenarios) are under discussion to improve its water quality and its ecological status. Scenarios include a large-scale mussel farm; the establishment of a local mussel farm that removes nutrients via harvest and increases water transparency; artificial mussel beds; groynes to reduce coastal current velocities, favor sediment accumulation, and promote the enlargement of macrophyte beds and other measures to enlarge macrophyte belts and coverage. We adapt and apply a computer aided ecosystem service assessment and visualization tool (ESAT). Eight experts and two student groups apply this tool and carry out an assessment of each scenario compared to the present state of the lagoon. The results show that the scenario assuming measures to enlarge macrophyte belts is perceived as the one that generates the highest additional ecosystem service output. However, more importantly our approach can serve as tool to catch the views of experts, can extract disagreements between experts and misunderstandings in the setup of scenarios as well as services that have highest priority for further consideration. Further, the results are useful for preparing stakeholder discussions and workshops. However, the expert assessments are influenced by the spatial scale of the assessed scenarios. As consequence, the assessment results itself cannot be regarded as a reliable basis for decision making. Today, Integrated Coastal Zone Management ideas and approaches are well reflected and integrated into Marine Spatial Planning and we show that a comparative ecosystem service assessment can be applied in different steps of each concept.